The Impact of Technology Readiness on Undergraduate Students’ Acceptance of Learning Management System - Maryani, Ika; Puspitasari, Yunita Mega (Journal of Education Technology, 2024)
The problem raised in this research is that there are no studies that measure the influence of technology readiness on student acceptance of the Learning Management System. This research aims to analyze the influence of technology readiness on acceptance of the Learning Management System among students. This research uses a quantitative approach with an ex post facto type. The research method uses associative research to determine the causal relationship between technological readiness and the Learning Management System. The data collection technique uses a technology readiness questionnaire and the Learning Management System which is then analyzed using simple linear regression analysis with t-test hypothesis testing. The questionnaire consists of 27 valid statements representing indicators, optimism, innovation, discomfort, insecurity, usefulness, ease of use, and interest in using. Questionnaires were distributed to students via WhatsApp using accidental sampling technique and obtained 152 respondents. The results show that 66.8% of acceptance of the Learning Management System is influenced by technology readiness. Meanwhile, 33.2% is influenced by other variables. The results of this research indicate that there is a positive influence of technology readiness on acceptance of the Learning Management System. This means that the higher the technological readiness, the higher the acceptance of the Learning Management System. The implication is that technological readiness must be improved to optimize the use of the Learning Management System. High acceptance of the Learning Management System can provide support for the success of the online learning process.